THE ROLE OF FORMAL AND INFORMAL ENVIRONMENTS IN SECOND LANGUAGE ACQUISITION OF STUDENTS - Ani Latifah; Zulaiha Zulaiha (English Education Study Program, 2023)
This study aims to answer why some students are more successful than others in mastering a second language and why one person seems to learn faster than the other even though both are in the same situation. This research is qualitative descriptive. The researcher interviewed five English teacher to find out the difference in the ability of students to master the second language, from those who only attended formal learning at school and took part in informal learning outside of school. The question consists of five questions. Because second language acquisition (L2) is a very complex process, there is no model that captures all its aspects. The researcher summarized the results of interviews with five English teachers, because the results of the interviews were almost the same. Based on the results of the study, it shows that students who only attend formal learning at school are different from students who are also supported by informal learning outside of school. Like taking a course, and also helping parents. Students who only study the second language at school will be slower in the process of obtaining a second language.